Qualitative Behavioral Assessment in Juvenile Farmed Atlantic Salmon (Salmo salar): Potential for On-Farm Welfare Assessment - Jarvis, Susan; Ellis, Maureen A.; Turnbull, James F.; Rey Planellas, Sonia; Wemelsfelder, Francoise (Frontiers in Veterinary Science, 2021)
There is a growing scientific and legislative consensus that fish are sentient, and therefore have the capacity to experience pain and suffering. The assessment of the welfare of farmed fish is challenging due to the aquatic environment and the number of animals housed together. However, with increasing global production and intensification of aquaculture comes greater impetus for developing effective tools which are suitable for the aquatic environment to assess the emotional experience and welfare of farmed fish. This study therefore aimed to investigate the use of Qualitative Behavioural Assessment (QBA), originally developed for terrestrial farmed animals, in farmed salmon and evaluate its potential for use as a welfare monitoring tool. QBA is a ‘whole animal’ approach based on the description and quantification of the expressive qualities of an animal’s dynamic style of behaving, using descriptors such as relaxed, agitated, lethargic, or confident. A list of twenty qualitative descriptors was generated by fish farmers after viewing video-footage showing behaviour expressions representative of the full repertoire of salmon in this context. A separate, non-experienced group of ten observers subsequently watched twenty-five video clips of farmed salmon, and scored the twenty descriptors for each clip using a Visual Analogue Scale (VAS). To assess intra-observer reliability each observer viewed the same twenty-five video clips twice, in two sessions 10 days apart, with the second clip set presented in different order. The observers were unaware that the two sets of video clips were identical. Data were analysed using Principal Component (PC) Analysis (correlation matrix, no rotation), revealing four dimensions that together explained 79% of the variation between video clips, with PC1 (tense/anxious/skittish – calm/mellow/relaxed) explaining the greatest percentage of variation (56%). PC1 was the only dimension to show acceptable inter- and intra-observer reliability, and mean PC1 scores correlated significantly to durations of slow and erratic physical movements measured for the same 25 video clips. Further refinements to the methodology may be necessary, but this study is the first to provide evidence for the potential of Qualitative Behavioural Assessment to serve as a time-efficient welfare assessment tool for juvenile salmon under farmed conditions.